Psychological features of labour motivation in Chinese teachers of the “Xing Ren” school - Yan In; Lida R. Pravdina; Yuliya V. Obukhova; Lyudmila А. Ovchinnikova (Rossijskij psihologičeskij žurnal., 2018)
The article focuses on the study of psychological features of labour motivation of Chinese teachers. The fact that motivation is the basis of the labor potential of the worker is well established today. In the education system the value of the human factor has increased in connection with the development of spiritual, intellectual, and creative potential of teaching and managerial workers. The paper overviews the history of the psychology of management in China. Wang Chongming stood at the origin of its main direction – the study of labour motivation. The reform of the education system in modern China, being a priority direction of the activity of the state, has caused the interest in teachers’ labour motivation. At the same time, in Chinese scientific and psychological publications very little information is available about the structure and features of teachers’ labour motivation. This explained the authors’ interest in the study at the “Xing Ren” school in Suihua City, Heilongjiang province. The empirical study involved 53 Chinese teachers of the school at the age from 23 to 58. The authors of article defined the essence of the “labour motivation” concept and demonstrated the specificity of a teacher’s work at a Chinese school. The labour motivation of Chinese teachers was characterized by prominent material motives and motives of responsibility, orientation on the value of happy family life and family safety, average involvement, predominance of motivation for success, and the need for being a source of professional career. The following characteristics of labour motivation reflected gender differences in Chinese teachers: relations, responsibility, and involvement (higher in women). The following characteristics of labour motivation reflected differences in the teachers of the humanities and natural sciences: power (higher in humanists), involvement, and motivation for success (higher in science teachers). The paper elaborates recommendations about the formation of the motivational system of Chinese schools.